Kajian Pustaka : Pemanfaatan Bahan Alam sebagai Pewarna Alami pada Sediaan Blush On - Nur Azizah Syahrna (Jurnal Farmasi UIN Alauddin Makassar, 2024)
ABSTRACT Introduction: Blush on is a beauty product known as blusher that can make the face look fresh and bright naturally. However, its main component, namely dyes, due to market competition encourages the misuse of dangerous dyes and can have side effects on its users. Objective: to obtain the content of active compounds from natural ingredients that can be used as natural dyes. Method: this study is a literature review of various research journals that have been published both nationally and internationally. Results: based on a literature review with the content of Anthocyanin compounds: Hibiscus sabdariffa L., Ipomoea batatas L. with Malus sp., Oryza nivara L, Rosa damascena P. Mill. Brassica Oleracea L. var. capitates f. rubra, Antidesma bunius L., Hylocereus polyrhizus, Tectona grandis LF, Garcinia mangostana L, Ixora paludosa (Blume) Kurz, Olanum betaceum, Fragaria vesca L, Syzygium cumini; Curcumin: Curcuma Longa; Betalain: Beta Vulgaris L; Kerotenoid: Gnetum gnemon L, Astaxanthin -Microalgae, Bixa Orellana L; and antarquinone; Morinda citrifolia L can be an alternative natural dye in blush on. Conclusion: the use of natural ingredients in the basic ingredients of blush on preparations can be used as a natural dye for the cheeks KEYWORDS: Blush on, coloring agent, natural dyes.